Penguatan Branding Aspek Gizi dan Kemasan Ole-Ole Kuliner Khas Indramayu (BROKU) dalam rangka menuju Pariwisata Kelas Dunia - Muh. Nur Hasan Syah; Prasetyo Hadi; Ibnu Malkan Bakhrul Ilmi; Utami Wahyuningsih; Arga Buntara; Fathiya Andara; Asriadi Masnar (Poltekita: Jurnal Pengabdian Masyarakat, 2023)
The reopening of tourism for tourists presents opportunities and challenges in improving the economy and public health status. The high potential of natural resources and tourism, combined with the lack of diversity in processing local food ingredients in Indramayu, requires action to maximize the management of local food ingredients from a technological aspect. This activity aims to improve the quality of Micro, Small, and Medium Enterprises (MSMEs) through guidance and assistance in ensuring the quality of each product menu offered to customers. The activity method consists of: Focus Group Discussions, Identification of Indramayu's Typical Souvenir Potentials, Hygiene-Sanitation Education and Assistance, as well as Nutrition Value Calculation and Packaging Design for one of the MSMEs, namely Abon Ikan Gabus. Based on community service activities that have been carried out, it was found that the potential of Indramayu's natural resources for producing nutritious souvenirs is still underutilized, and there is a need to increase knowledge about hygiene and sanitation in food service, as well as information about product nutrition values and attractive product packaging design. Therefore, it is concluded that the potential of Indramayu's typical souvenir products is high, with the availability of local food ingredients, adequate knowledge with branding for nutrition and packaging. Continuous guidance efforts and increasing the number of involved MSMEs need to be carried out.